2013
DOI: 10.1117/1.jbo.18.4.046014
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Mueller polarimetric imaging detecting residual cancer and cancer regression after neoadjuvant treatment for colorectal carcinomas

Abstract: Abstract. This work is devoted to a first exploration of Mueller polarimetric imaging for the detection of residual cancer after neoadjuvant treatment for the rectum. Three samples of colorectal carcinomas treated by radiochemotherapy together with one untreated sample are analyzed ex vivo before fixation in formalin by using a multispectral Mueller polarimetric imaging system operated from 500 to 700 nm. The Mueller images, analyzed using the Lu-Chipmann decomposition, show negligible diattenuation and retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(103 citation statements)
references
References 33 publications
0
100
0
1
Order By: Relevance
“…The MMPD method proposed by Lu and Chipman is based on the three main interactions between the polarized light and media: diattenuation (D), retardation (δ), and depolarization (Δ) [32]. The MMPD parameters representing the polarization properties are not sensitive to the azimuthal orientation of the sample and have been applied to studies of various cancerous tissues including the detection of cervical cancer [33], colon cancer [23], and skin cancer [21]. In this study, we use the linear retardance (δ) and its orientation angle (θ), which can be derived from the decomposed Mueller matrix (M) shown as Eq.…”
Section: Mueller Matrix Polar Decomposition and Mueller Matrix Transfmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMPD method proposed by Lu and Chipman is based on the three main interactions between the polarized light and media: diattenuation (D), retardation (δ), and depolarization (Δ) [32]. The MMPD parameters representing the polarization properties are not sensitive to the azimuthal orientation of the sample and have been applied to studies of various cancerous tissues including the detection of cervical cancer [33], colon cancer [23], and skin cancer [21]. In this study, we use the linear retardance (δ) and its orientation angle (θ), which can be derived from the decomposed Mueller matrix (M) shown as Eq.…”
Section: Mueller Matrix Polar Decomposition and Mueller Matrix Transfmentioning
confidence: 99%
“…The previous literature shows that more than 85% of cancers originate from the superficial epithelium, which means that polarization imaging methods have great potential in screening and identifying cancer at an early stage [19,20]. Therefore, Mueller matrix polarimetry has been used to assist the diagnosis of various cancerous tissues, such as skin cancer [21], cervical cancer [22], colon cancer [23], liver cancer [24,25], and so on [26,27]. Recently, we have designed a Mueller matrix microscope by adding a polarization state generator and analyzer (PSG and PSA) to a commercial transmission-light microscope and applied it to detect human liver and cervical cancerous tissues with fibrosis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from polarization, spectral features of the scattered light also carry information on the microstructure of biological samples, therefore can be applied in diagnosis of cancerous tissues [19]. Studies have shown that combining polarization and spectral techniques can provide more powerful tools for cancer diagnosis [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic polarization information of interest is carried by a 4 3 4 matrix named a Mueller matrix and this can be experimentally obtained from Mueller polarimetry and polarimetric imaging. In recent years, an increasing number of biomedical applications of Mueller polarimetric imaging techniques have been proposed [5], e. g. oral cancerous legion detection [13], cervical cancer and colon cancer detection and staging [12,[14][15][16][17][18][19], assessment of cancer therapy [20], partial bladder obstruction diagnosis [21], guiding mass spectrometry for instant pathology [22], characterizing collagen fibres [23], and these have demonstrated advantages over polarization blind imaging.…”
Section: Introductionmentioning
confidence: 99%